"Fou rire prodromique" as the presentation of pontine ischaemia secondary to vertebrobasilar stenosis. Issue 6 (1st December 2001) - Gondim, F de A A; Parks, B J; Cruz-Flores, S
Abstract : "Fou rire prodromique" (prodrome of crazy laughter) is a rare form of pathological laughter of uncertain pathophysiology. A patient is presented with pathological laughter as the first manifestation of pontine ischaemia due to vertebrobasilar stenosis. A 65 year old man developed uncontrollable and unemotional laughter for almost an hour followed by transient right facial-brachial paresis. He had fluctuation of laughter, right facial brachial paresis, and occasional crying. Magnetic resonance imaging, magnetic resonance angiogram (MRA), and an angiogram showed small left pontine and cerebellar infarcts, left vertebral artery occlusion, and right vertebral and basilar artery stenosis. His condition deteriorated to bilateral brain stem infarction and he died. Necropsy confirmed the extensive brain stem infarction. Pathological laughter can be the very first presenting manifestation of ischaemia of the ventrotegmental junction of the upper pons. It is hypothesised that the pathological laughter in this patient was secondary to ischaemic ephaptic stimulation of the descending corticopontine/ bulbar pathways.